1998
DOI: 10.1029/98jd02275
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of lake ice phenology and climate: Model simulations and observations

Abstract: Abstract. Lake ice phenology parameters (dates of ice onset and thaw) provide an integrative climatic description of autumn to springtime conditions. Interannual variations in lake ice duration and thickness allow estimates of local climatic variability. In addition, long-term changes in lake ice phenology may provide a robust indication of climatic change. The relationship between lake ice and climate enables the use of process-based models for predicting the dates of freeze-up and thaw. LIMNOS (Lake Ice Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
66
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 27 publications
(27 reference statements)
1
66
1
Order By: Relevance
“…Examples of the former include the work by a) Vavrus et al (1996) who tested the sensitivity of lake-ice phenology for three lakes in Wisconsin, USA, to variable climate inputs using a numerical lake-ice model, LIMNOS and found that simulated ice-off date is more sensitive to air temperature changes than the ice-on date; b) Menard et al (2002) and Duguay et al (2003) who used the one-dimensional thermodynamic lake-ice model CLIMo to simulate ice-growth processes on sub-arctic lakes showing that lake morphometry, depth in particular, is a determinant of ice-off dates for shallow lakes at high latitudes, and c) Gao and Stefan (2004) who incorporated the water temperature and lake-ice model MINILAKE to simulate the impact of 2 × CO 2 climate scenario on ice characteristics of five north American lakes and concluded that lake-ice duration would be reduced by 25-33 days, and maximum ice thickness by 18-30 cm. In terms of broader regional analyses, Walsh et al (1998) used a modified form of the LIMNOS model on a 0.5 × 0.5°latitude-longitude grid over the Northern Hemisphere to simulate lake-ice phenology of hypothetical lakes with mean depths of 5 and 20 m. Changes, however, were only modelled using monthly air temperature values and hence, could not properly represent the physical dynamics in lake thermal budgets controlling ice formation, growth, and ablation. Williams et al (2004) analysed lake-ice data for 143 North American freshwater lakes and applied single variable linear regression and factor analysis methods to determine correlations with air temperature, lake morphometry, latitude, and topographic elevation, and used the derived relationships to estimate the effects of 1°C rise in average air temperature on lake-ice characteristics to be that, ice-in date occurs 5 days later, ice-out date occurs 6 days earlier, and maximum ice thickness is reduced by 7 cm.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the former include the work by a) Vavrus et al (1996) who tested the sensitivity of lake-ice phenology for three lakes in Wisconsin, USA, to variable climate inputs using a numerical lake-ice model, LIMNOS and found that simulated ice-off date is more sensitive to air temperature changes than the ice-on date; b) Menard et al (2002) and Duguay et al (2003) who used the one-dimensional thermodynamic lake-ice model CLIMo to simulate ice-growth processes on sub-arctic lakes showing that lake morphometry, depth in particular, is a determinant of ice-off dates for shallow lakes at high latitudes, and c) Gao and Stefan (2004) who incorporated the water temperature and lake-ice model MINILAKE to simulate the impact of 2 × CO 2 climate scenario on ice characteristics of five north American lakes and concluded that lake-ice duration would be reduced by 25-33 days, and maximum ice thickness by 18-30 cm. In terms of broader regional analyses, Walsh et al (1998) used a modified form of the LIMNOS model on a 0.5 × 0.5°latitude-longitude grid over the Northern Hemisphere to simulate lake-ice phenology of hypothetical lakes with mean depths of 5 and 20 m. Changes, however, were only modelled using monthly air temperature values and hence, could not properly represent the physical dynamics in lake thermal budgets controlling ice formation, growth, and ablation. Williams et al (2004) analysed lake-ice data for 143 North American freshwater lakes and applied single variable linear regression and factor analysis methods to determine correlations with air temperature, lake morphometry, latitude, and topographic elevation, and used the derived relationships to estimate the effects of 1°C rise in average air temperature on lake-ice characteristics to be that, ice-in date occurs 5 days later, ice-out date occurs 6 days earlier, and maximum ice thickness is reduced by 7 cm.…”
Section: Introductionmentioning
confidence: 99%
“…While most work involving ice cover changes has been done for specific locations, Walsh et al (1998) produced gridded ice phenology for the entire Northern Hemisphere using historical mean climate data to create the first wide-scale examination of lake ice phenology. A recent study using climate model output examining possible changes to the lake ice regime in North America from 40 • N to 75 • N under future climates suggests break-up will advance by 10-20 days, while freezeup will be delayed by 5-15 days, resulting in a reduction of the ice cover duration by 15-35 days (Dibike et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about the year-round ecological and biogeochemical traits of typical freshwater microorganisms is required to understand when and where certain microorganisms will appear and how they will influence other organisms or biogeochemical processes and, hence, water quality. Together, this information will improve our ability to predict and model freshwater ecosystem and biogeochemical dynamics and to determine their role in the landscapes in the face of environmental change.A large number of lakes, particularly those situated at high altitude and the numerous high-latitude lakes in the temperate and boreal climate zones, are seasonally covered by ice for more than 40% of the year (Walsh et al 1998). Despite this, surprisingly little is known about the ecology, diversity, and metabolism of microorganisms that reside under the ice cover in such lakes (Salonen et al 2009).…”
mentioning
confidence: 99%
“…A large number of lakes, particularly those situated at high altitude and the numerous high-latitude lakes in the temperate and boreal climate zones, are seasonally covered by ice for more than 40% of the year (Walsh et al 1998). Despite this, surprisingly little is known about the ecology, diversity, and metabolism of microorganisms that reside under the ice cover in such lakes (Salonen et al 2009).…”
mentioning
confidence: 99%